1989
DOI: 10.1002/1097-0142(19891201)64:11<2399::aid-cncr2820641134>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors, curative therapies, and behavioral outcomes. A comparison of testis cancer survivors and a control group of healthy men

Abstract: In a retrospective study of 223 testis cancer survivors and 120 controls matched sociodemographically, we examined the relative impact of sociodemographic and clinical factors on long-term outcomes in the areas of sexual function, relationships, employment, and mental outlook. For most of the survivors, testis cancer did not lead to unemployment (4.5%), divorce (6.8%), or disabling psychological problems. Multivariate analysis results confirm that cancer survivors report significantly more infertility and sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 25 publications
7
77
0
1
Order By: Relevance
“…Prior studies [4][5][6][7][8][9][10][11][12] have suggested that the overall frequency of divorce in cancer patients (range, 5-17%) does not differ from that of well-matched controls in the general population. Our results are consistent with this observation, revealing an overall frequency of divorce (11.6%) in the 3 patient cohorts representing >500 patients diagnosed with serious neurologic and oncologic illnesses.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Prior studies [4][5][6][7][8][9][10][11][12] have suggested that the overall frequency of divorce in cancer patients (range, 5-17%) does not differ from that of well-matched controls in the general population. Our results are consistent with this observation, revealing an overall frequency of divorce (11.6%) in the 3 patient cohorts representing >500 patients diagnosed with serious neurologic and oncologic illnesses.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have in fact suggested that men are less able to undertake a caregiving role and assume the burdens of home and family maintenance compared with women. [3][4][5][6][7][8][9][10][11] Thus, a woman becomes willing sooner in the marriage to commit to the burdens of having a sick spouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Danish cohort study suggested that cancer patients face the same challenges with regard to divorce as people who have never been confronted with cancer (Carlsen et al, 2007). Moreover, studies suggest that some couples find that cancer strengthens their relationship (Rieker et al, 1989;Schover and von Eschenbach, 1985). Other studies show, however, that some special cancers such as breast cancer and cervix cancer result in marital disruption.…”
Section: Gender Differences In Marital Disruption Among Patients Withmentioning
confidence: 99%
“…Lower educational level and occupational status were also associated with higher sexual performance distress [35]. In a study of cancer survivors of many cancer types, Taskila et al reported that male cancer survivors with less than a college degree and lower occupational status had a greater need for support in the workplace and from occupational health personnel [31].…”
Section: Sep and Survivorshipmentioning
confidence: 99%